Analytical Study of Electronic Leaning Reality from The Faculty Point of View During COVID 19 Pandemic - Flaeeh, Duha Jabber (Journal of Physical Education, 2022)
The research aimed at identifying the effect of electronic learning in preparatory schools from faculty point of view who used e- learning during COVID 19 pandemic. It also aimed at recognizing the obstacles that the members of the faculty face through an open questioner for physical education male and female teachers who used e – learning. The answers were rearranged consisting ten items related to e – learning proficiency and the other items dedicated for obstacle in e – learning. The researcher used the descriptive method on (100) male teachers and (50) female teachers. The results showed differences in means, standard deviations due to advantages as well as disadvantages of e – learning.